The Role of career and knowledge management in retention - Dajnoki, Krisztina; Szondi, Réka; Filep, Roland (Studia Mundi – Economica, 2021)
Rapid response to changing environmental challenges plays a crucial role in maintaining competitiveness. For HR, achieving employee loyalty is one of the essential tasks that can solve the difficulties of the labour shortage. Retaining key workers is a growing problem today while attracting the right talented workforce to the organisation is critical. Employee satisfaction influences the level of loyalty, with the necessary recognition and appreciation of the individual’s work, clear goals and expectations and the existence of a supportive organisational culture. Organisations’ workforce retention capabilities are often linked to managerial attitudes, to the quality and systematic development of HR systems. The purpose of this study is to summarise and support, based on international literature and research, the importance of two key functions, career and knowledge management, for retention. As a result of the research, it is possible to determine the advantage of applying the two critical functions in retention management, and the difficulties and risk factors arising during the process can be defined. If the company does not focus on motivating its employees, it will significantly increase its costs as well as the time and energy invested in recruiting and selecting new employees. In conclusion, in addition to expanding the use of HR functions, successful loyalty increasing techniques include a career plan that supports both individual and organisational goals and an organisational culture that encourages knowledge sharing.